2009
DOI: 10.1096/fj.09-136291
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics: methylation‐associated repression of heparan sulfate 3‐O‐sulfotransferase gene expression contributes to the invasive phenotype of H‐EMC‐SS chondrosarcoma cells

Abstract: Heparan sulfate proteoglycans (HSPGs), strategically located at the cell-tissue-organ interface, regulate major biological processes, including cell proliferation, migration, and adhesion. These vital functions are compromised in tumors, due, in part, to alterations in heparan sulfate (HS) expression and structure. How these modifications occur is largely unknown. Here, we investigated whether epigenetic abnormalities involving aberrant DNA methylation affect HS biosynthetic enzymes in cancer cells. Analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 65 publications
0
57
1
1
Order By: Relevance
“…11,15,31 Our study shows that 3-OST3A was repressed and subjected to hypermethylation in all breast cancer cell lines tested except in HER2+-SKBR3 cells in which, consistently, it was expressed at relatively high level. Further analysis of the chromatin interactors at the 3-OST3A promoter showed that the epigenetic regulation not only depends upon DNA methylation, but also on repressive histone marks, and involves the recruitment of PcG proteins.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…11,15,31 Our study shows that 3-OST3A was repressed and subjected to hypermethylation in all breast cancer cell lines tested except in HER2+-SKBR3 cells in which, consistently, it was expressed at relatively high level. Further analysis of the chromatin interactors at the 3-OST3A promoter showed that the epigenetic regulation not only depends upon DNA methylation, but also on repressive histone marks, and involves the recruitment of PcG proteins.…”
Section: Discussionmentioning
confidence: 65%
“…Prompted by studies from us and others pointing to an epigenetic control of 3-OST genes 11,15 , we determined whether 3-OST3A was regulated epigenetically in breast cancer cells. 3 DNA methylation analysis of the 3-OST3A promoter CpG island ( Figure S1A) showed strong hypermethylation in T-47D and MDA-derived cells, while in MCF-7 cells, hypermethylation only occurred downstream from the TSS ( Figure 1B).…”
Section: --Ost3a Is Differentially Repressed In Breast Cancer Cell Lmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA hypermethylation contributes to the development of CS via various cell pathways, including cell cycle, apoptosis, cell adherence and cell-to-cell interaction [25][26][27][28]. For example, P16 INK4a , a well-known tumor suppressor gene, was found to be hypermethylated in the promoter region in CS [26].…”
Section: Dna Hypermethylation and Abnormalities In Csmentioning
confidence: 99%
“…Furthermore, gene silencing induced by DNA hypermethylation is involved in cell-to-cell interaction in CS. Heparan sulfate (HS) proteoglycan is a core protein linked by long linear glycosaminoglycan HS located on the surface of almost every animal cell, and interacts with numerous biological molecules, such as growth factors and cytokines [28,30]. Thereby, HS proteoglycans regulate a number of biological processes, including cell proliferation, migration and adhesion.…”
Section: Dna Hypermethylation and Abnormalities In Csmentioning
confidence: 99%